Answer:
colby
hourly rate =$8.90
overtime rate = time and a half = 1.5
the hourly overtime rate is the product of the overtime rate and the hourly rate.
hourly overtime rate= overtime rate × hourly rate
= 1.5 × $8.90
= $13.35
Cheryl
hourly rate = $7.10
overtime rate = double time = 2
the hourly overtime rate is the product of overtime rate and the hourly rate.
hourly overtime rate = overtime rate × hourly rate
= 2 × $7.10
= $14.20
<h3>Comparison</h3>
we note that the hourly overtime rate of cheryl is higher than the hourly overtime rate of colby, which implies that cheryl earns more for one hour of overtime.
we are also interested in the difference of the hourly overtime rate:
hourly overtime rate colby — hourly overtime rate cheryl
= $14.20 – $13.35
= $0.85
thus cheryl earns $0.85 more for one hour of overtime than colby .
<h3>result</h3>
<h2>cheryl,$0.85</h2>
그것이 당신에게 도움이되기를 바랍니다 :)
가장 똑똑한 것으로 표시하십시오 :)
좋은 하루 되세요 :)
Answer:
The surface area of the figure = 962 ft²
Step-by-step explanation:
The rectangle dimensions and its area given below
Dimensions Number Area
12 x 7 2 12 x 7 x 2 = 168
16 x 7 1 16 x 7 = 112
12 x (16 + 5) 1 12 x 21 = 252
16 x 12 1 16 x 12 = 192
16 x 13 1 16 x 13 = 208
Triangle dimensions
Dimensions Number Area
b = 12 & h = 5 2 bh/2 = (12*5)/2 = 30
To find total area
Total area = 168 + 112 + 252 + 192 + 208 + 30 = 962 ft²
The value of the given expression (3m - n)² + 4m when m = 63 and n = 45 is equal to 20,916.
<h3>What is an expression?</h3>
An expression can be defined as a mathematical equation which is used to show the relationship existing between two or more variables and numerical quantities.
<u>Given the following variables:</u>
Substituting the given variables into the given expression, we have;
Expression = (3m - n)² + 4m.
Expression = (3(63) - 45)² + 4(45).
Expression = (189 - 45)² + 180
Expression = 144² + 180
Expression = 20,736 + 180
Expression = 20,916.
Read more on expressions here: brainly.com/question/28260012
#SPJ1
Complete Question:
Evaluate the expression when m = 63 and n = 45. (3m - n)² + 4m.
Answer:
64
Step-by-step explanation:
Evaluate x^4 + 3 x^3 - 6 x^2 - 12 x - 8 where x = 3:
x^4 + 3 x^3 - 6 x^2 - 12 x - 8 = 3^4 + 3×3^3 - 6×3^2 - 12×3 - 8
3^3 = 3×3^2:
3^4 + 3×3×3^2 - 6×3^2 - 12×3 - 8
3^2 = 9:
3^4 + 3×3×9 - 6×3^2 - 12×3 - 8
3×9 = 27:
3^4 + 3×27 - 6×3^2 - 12×3 - 8
3^2 = 9:
3^4 + 3×27 - 69 - 12×3 - 8
3^4 = (3^2)^2:
(3^2)^2 + 3×27 - 6×9 - 12×3 - 8
3^2 = 9:
9^2 + 3×27 - 6×9 - 12×3 - 8
9^2 = 81:
81 + 3×27 - 6×9 - 12×3 - 8
3×27 = 81:
81 + 81 - 6×9 - 12×3 - 8
-6×9 = -54:
81 + 81 + -54 - 12×3 - 8
-12×3 = -36:
81 + 81 - 54 + -36 - 8
81 + 81 - 54 - 36 - 8 = (81 + 81) - (54 + 36 + 8):
(81 + 81) - (54 + 36 + 8)
| 8 | 1
+ | 8 | 1
1 | 6 | 2:
162 - (54 + 36 + 8)
| 1 |
| 5 | 4
| 3 | 6
+ | | 8
| 9 | 8:
162 - 98
| | 15 |
| 0 | 5 | 12
| 1 | 6 | 2
- | | 9 | 8
| 0 | 6 | 4:
Answer: 64
13 + 49 = 62
62 - 12 = 50
The answer is 50